Dating the Brazilian Economy’s Business Cycle: 1997-2009 - Almeida Júnior, Antonio Carneiro de; Almeida, Lucas Milanez de Lima (História Econômica & História de Empresas, 2025)
A group of Marxian economists has been dating the Brazilian economy’s business cycle from the first overproduction crisis in 1962 to the present. Their research is based on the Mendonça-Ribeiro interpretation of Marx’s crisis theory. This study builds upon their work with the purpose of contributing to bringing the research up to date. We examined Brazil’s fifth business cycle. The cyclical component of Brazil’s GDP was obtained using the Baxter-King filter. Taking said component as reference, secondary data was manipulated and analyzed to identify the main characteristics of each period in order to divide the business cycle into stages according to Marx’s classification. We reached the conclusion that the referred cycle can be divided into 1997.Q3-2000.Q1: crisis; 2000.Q2-2002.Q1: depression; 2002.Q2-2005.Q4: recovery; 2006.Q1-2008.Q1: peak. Furthermore, our analysis identified abnormal economic fluctuations during the depression and recovery stages. We also verified that excess conservatism in the monetary policy carried out by the Brazilian Central Bank could have prevented capital accumulation from reaching the speed it would in normal conditions. At last, we highlighted some important characteristics of the crisis that mark the beginning of the next cycle.